"...with their usual cunning": gleaning architectural tactics from 1860s warfighting pa [paa] [pah]" - Schmidt, Tyson (Architectural History Aotearoa, 2010)
Pā have been reaped by other disciplines. Archaeologists have poured over them like coroners, enquiring into what was and how it came to be, dissecting the typology, studying and debating its purposes, its uses, its spread, its numbers. Military historians have drilled into the role pā played in individual battles, campaigns, and even distant conflicts. Architecture prefers the whare, with only a handful of architects fossicking around pā – Sarah Treadwell’s enquiry into Gate Pa, Amanda Yates’ examination of monumental interior, Rewi Thompson’s and Royal Associates’ referencing of parts of pā in their work. This article extends the architectural fossicking by looking at what can be learnt from warfighting pā of the 1860s – a decade where they reached a nadir of design and use as a result of cultural conflict.